The satellite SMILE – its prospects for observing cosmic sources - Vojtěch Šimon; René Hudec; Andrew Read (Acta Polytechnica)
We describe the scientific potential of a Soft X-ray Imager (SXI) onboard the ESA–CAS satellite SMILE to study the activity of cosmic X-ray sources in the soft X-ray region and located in the fields planned to be observed by SXI. We used the 2–3 keV band flux of the monitor MAXI/ISS, covering at least part of the expected band of the SXI/SMILE telescope. We discuss how SXI can contribute to this branch and how combining the SXI/SMILE data with those obtained by other satellites on the same days can be helpful if the light curves of the 1-day means are used. We show these possibilities on several examples of cosmic X-ray sources (Vela X-1 and GROJ1008-57 containing neutron stars accreting matter from their companions) in the field of view of SXI. Including observations from MAXI/ISS and BAT/Swift will enable extending the coverage to the energy of 50 keV.